Purity assessment and determination of sertaconazole in bulk and pharmaceutical formulations based on spectrophotometric and chromatographic approaches - Abou Al Alamein, Amal Mahmoud (European Journal of Chemistry, 2015)
Stability evaluation of the drug substance is an integral part of the systematic approach to stability studies. Hence, three simple, sensitive and precise methods depending on two different techniques as UV spectrophotometry and chromatography were adopted for the task of stability indicating determination of sertaconazole (SER) in presence of its acidic degradation products. The first method is Zero-crossing first derivative (1D) spectrophotometric one, which allows the determination of SER over a concentration range of 4-64 µg/mL at 290 nm with mean percentage recoveries 99.77±0.781. While first-derivative of the ratio spectra (1DR) is the method of choice for determination of pure SER at a maximum 300 nm and at a trough 304 nm, with mean percentage recoveries 99.98±0.720 and 100.46±0.640, respectively. The third developed HPLC method used a RP-ZORBAX C18 column (5 μm particle size, 250×4.6 mm; id) with isocratic elution. The mobile phase was methanol: 0.2% formic acid aqueous solution (75:25, v:v); pH = 3.5 at the flow rate of 1.0 mL/min, with UV detection at 260 nm. The method could determine SER in the range of 0.8-40 µg/mL with a mean percentage recovery of 99.65±0.630. The developed methods were succeeded in the determination of SER in bulk powder, pharmaceutical dosage forms and in presence of its acidic degradation products. The results obtained were validated in compliance with ICH guidelines and compared statistically with each other and to those of the official method in the British Pharmacopoeia regarding both accuracy and precision.